Addiction stigma and the production of impediments to take-home naloxone uptake. (March 2022) - Fomiatti, Renae; Farrugia, Adrian; Fraser, Suzanne; Dwyer, Robyn; Neale, Joanne; Strang, John
Opioid overdose deaths are a major health issue in Australia and around the world. Programmes to provide opioid consumers with 'take-home' naloxone to reverse overdose exist internationally, but uptake by mainstream health services and consumers remains inconsistent. Researchers have identified a range of important educational, training and logistical impediments to take-home naloxone uptake and distribution, yet they have focused less on the social dynamics that can enhance or limit access, such as stigma. In this article, we also explore impediments to uptake, drawing on qualitative interview data gathered for an Australian research project on take-home naloxone. Mobilising a performative approach to stigma, we argue that overdose and prevention are shaped by the social dynamics of stigma and, as such, responsibility for dealing with overdose, as with take-home naloxone, should also be considered social (i.e. shared among peers, the public, communities and governments). Our interview data illuminate the various ways in which addiction stigma limits the possibilities and capacities of take-home naloxone and overdose prevention. First, we focus on how stigma may impede professional information provision about take-home naloxone by limiting the extent to which it is presented as a matter of interest for all opioid consumers, not just those who consume opioids illicitly. Second, we explore how stigma may limit the scale-up and expansion of programmes and access points. From here, we focus on how stigma co-constitutes the politics of overdose and prevention, rendering take-home naloxone ill-suited to many social settings of overdose. In closing, we point out that stigma is not just a post hoc impediment to access to and use of take-home naloxone but is central to opioid overdose production itself, and to effective prevention. While take-home naloxone is an excellent life-saving initiative, uncritically valorising it may divert attention from broader goals, such as the de-stigmatisation of drug consumption through decriminalisation, and other ambitious attempts to reduce overdose.